Pre-diagnosis Dietary One-Carbon Metabolism Micronutrients Consumption and Ovarian Cancer Survival: A Prospective Cohort Study - Xu, He-Li; Gong, Ting-Ting; Liu, Fang-Hua; Wei, Yi-Fan; Chen, Hong-Yu; Yan, Shi; Zhao, Yu-Hong; Gao, Song; Jiao, Yi-Sheng; Wu, Qi-Jun (Frontiers in Nutrition, 2022)
Background & aims: Epidemiological evidence on the relation between one-carbon metabolism (OCM) micronutrients intake and ovarian cancer (OC) survival are limited and conflicting. We evaluated the aforementioned associations in a prospective cohort-the Ovarian Cancer Follow-Up Study. Methods: A total of 635 newly diagnosed OC patients aged 18-79 y were enrolled in the present study. Dietary intake related to one-carbon metabolism, including methionine, vitamins B2, B3, B6, B9, B12, choline, and betaine, was assessed using a validated 111-item food frequency questionnaire. Deaths were ascertained until March 31, 2021, via medical records and active follow-up. Cox proportional hazards regression model was used to evaluate the hazard ratios (HRs) and 95% confidence intervals (CIs) for these aforementioned associations. Results: During a median follow-up of 37.2 months (interquartile: 24.7-50.2 months), 114 deaths were identified. We observed an improved survival with the highest compared with the lowest tertile of dietary vitamin B6 (HR=0.52, 95%CI: 0.32-0.84, P-trend <0.05) and choline intake (HR=0.50, 95%CI: 0.30-0.83, P-trend <0.05). No significant associations with OC survival were observed for dietary vitamins B2, B3, B9, B12, methionine, and betaine intake. We also observed a curvilinear association between vitamin B6 intake and OC survival (P nonlinear <0.05). Conclusion: Our study suggests that pre-diagnosis higher intake of vitamin B6 and choline may improve OC survival. Further clarification of these associations is warranted.